2015
DOI: 10.3989/mc.2015.01614
|View full text |Cite
|
Sign up to set email alerts
|

Use of bottom ash from thermal power plant and lime as filler in bituminous mixtures

Abstract: This study focuses on the characterization of bottom ash (PCC-BA) and determining the mechanical characteristics of hot mix asphalt (HMA) using PCC-BA and hydrated lime (HL) as filler. Physical and chemical characterization of the bottom ash was carried out to evaluate its eventual reutilization as filler substitute. The materials tested in this study were made using 0%, 25%, 50%, 70% and 100% of PCC-BA combined with HL. HMA mixes were evaluated in terms of their engineering properties, namely: air voids in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
5
1
2
Order By: Relevance
“…A higher value indicates a longer lifespan and better performance of the pavement. The pavement containing 30% hydrated lime and 70% bottom ash had the highest density, which is the recommended density for the road surface and intermediate layers with small infrastructures and light traffic [86]. However, the results of this research are contrary to the findings of an earlier study [85], which showed that using bottom ash as a filler substitute resulted in a higher rutting potential and a lower dynamic modulus than the control mixture.…”
Section: Pavement Constructioncontrasting
confidence: 92%
See 1 more Smart Citation
“…A higher value indicates a longer lifespan and better performance of the pavement. The pavement containing 30% hydrated lime and 70% bottom ash had the highest density, which is the recommended density for the road surface and intermediate layers with small infrastructures and light traffic [86]. However, the results of this research are contrary to the findings of an earlier study [85], which showed that using bottom ash as a filler substitute resulted in a higher rutting potential and a lower dynamic modulus than the control mixture.…”
Section: Pavement Constructioncontrasting
confidence: 92%
“…Other studies assessed the potential of using CBA as a filler in bituminous mixtures [85,86]. The high porosity and high specific surface properties of hydrated lime and/or bottom ash increased the value for the optimum binder content.…”
Section: Pavement Constructionmentioning
confidence: 99%
“…In this respect, it is worth noting that bituminous mixtures have a certain damping due to their partly viscous nature, and this should be taken into account when determining the resonance frequency. Therefore, the natural frequency (f n ) that will be used in the calculation of the modulus must be calculated from the frequency obtained in the measure (f d ) [2] (13).…”
Section: Testing Planmentioning
confidence: 99%
“…This is also the main reason why new elements such as polymers, crumb rubber or thermal power plant ashes (1,2) are being incorporated into bituminous mixtures, in order to achieve more durable pavements that have minimal impact on economic and social activities. In this respect, determining the degree of deterioration of the materials used in the construction of these infrastructures can be of considerable value when attempting to identify the suitability of these new components and the optimal time to conduct rehabilitation activities.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, replacing the natural aggregate with alternative materials is another strategy widely used. Thus, recycled asphalt pavement (RAP) from roads [3], by-products [4,5] or construction waste [6] are some of the materials used in bituminous mixtures to replace natural aggregate, although other are also standing out, as rubber from end-of-life tires [7,8] and other polymers [9,10], which can also be used to improve the mechanical performance of the bituminous mixtures.…”
Section: Introductionmentioning
confidence: 99%